Swiss Sepsis National Action Plan: A coordinated national action plan to stop sepsis-related preventable deaths and to improve the support of people affected by sepsis in Switzerland - Schlapbach, Luregn J.; Zimmermann, Elisa A.; Meylan, Sylvain; Stocker, Martin; Suter, Peter M.; Jakob, Stephan M.; National Action Plan Working Group, on behalf of the Swiss Sepsis (Frontiers in Medicine, 2023)
Background Sepsis is a devastating disease which causes yearly over 10 million deaths worldwide. In 2017, the World Health Organization (WHO) issued a resolution prompting member states to improve the prevention, recognition, and management of sepsis. The 2021 European Sepsis Report revealed that—contrary to other European countries—Switzerland had not yet actioned the sepsis resolution. Methods A panel of experts convened at a policy workshop to address how to improve awareness, prevention, and treatment of sepsis in Switzerland. Goal of the workshop was to formulate a set of consensus recommendations toward creating a Swiss Sepsis National Action Plan (SSNAP). In a first part, stakeholders presented existing international sepsis quality improvement programs and national health programs relevant for sepsis. Thereafter, the participants were allocated into three working groups to identify opportunities, barriers, and solutions on (i) prevention and awareness, (ii) early detection and treatment, and (iii) support for sepsis survivors. Finally, the entire panel summarized the findings from the working groups and identified priorities and strategies for the SSNAP. All discussions during the workshop were transcribed into the present document. All workshop participants and key experts reviewed the document. Results The panel formulated 14 recommendations to address sepsis in Switzerland. These focused on four domains, including (i) raising awareness in the community, (ii) improving healthcare workforce training on sepsis recognition and sepsis management; (iii) establishing standards for rapid detection, treatment and follow-up in sepsis patients across all age groups; and (iv) promoting sepsis research with particular focus on diagnostic and interventional trials. Conclusion There is urgency to tackle sepsis. Switzerland has a unique opportunity to leverage from lessons learnt during the COVID-19 pandemic to address sepsis as the major infection-related threat to society. This report details consensus recommendations, the rationale thereof, and key discussion points made by the stakeholders on the workshop day. The report presents a coordinated national action plan to prevent, measure, and sustainably reduce the personal, financial and societal burden, death and disability arising from sepsis in Switzerland.